Pemberdayaan Masyarakat Pengangguran di Kawasan Lereng Argopuro untuk Pengembangan Ekonomi Lokal - Rachmat Udhi Prabowo; Dimas B. Bastara; Chairul Saleh; Dyah Ayu Nugraheni; Kuni Z. Barikah; Eliene Br. Simatupang (Institut Pertanian Bogor, 2025)
The slopes of Mount Argopuro are naturally rich in inactive volcanoes in Indonesia. The surrounding community uses this area as a place for economic livelihoods. One of the dominant economic sectors in which the surrounding community chooses to meet its living needs is the agricultural sector, particularly the livestock sector. Community empowerment activities aim to 1) Increase understanding of business innovation to increase the added value of managing livestock waste; 2) Build pioneering business institutions through Community Business Groups; and 3) Initiate business marketing and sustainability. The method of implementing community empowerment includes socialization and training with four criteria: 1) Providing material on the importance of institutions; 2) Product diversity as a requirement for developing livestock waste processing businesses; 3) Business Development Practices; and 4) Strengthening business management. Community empowerment activities are equipped with activity evaluation methods through surveys that provide pre-test and post-test treatments to the unemployed community in Panti Village. The results of the Community Service show that the unemployed community in Panti Village can understand the benefits of strengthening institutions based on business legality and the creation of AD/ART as a basic requirement for the formation of institutions. The unemployed community can know, understand, and develop skills in the diversity of livestock waste processing that have not been utilized either economically or ecologically. An unemployed community can create packaging designs, promotions, networking, social media accounts, product trust concepts, and management to improve business performance. To improve the sustainability of the program and product absorption, the community empowerment team cooperates based on business transparency with the business incubator of the Faculty of Economics and Business Laboratory, University of Jember to improve networking and product expansion in the future.